Comparison of Uncomfortable Loudness Level in Stapedotomy with or without Stapedial Tendon Preservation (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Otosclerosis is one of the commonest diseases of the ear mostly involves the otic capsule. Most often otosclerotic foci appear in stapes region leading to stapes fixation, predominantly affect the adolescence female. The most common presenting symptom of clinical otosclerosis is conductive deafness. The mainstay of treatment for otosclerosis is surgery. Surgical options include stapedectomy, stapedotomy with or without stapedial tendon preservation. The latter being is the procedure of choice.Aim: The aim of this study is to compare the outcome of uncomfortable loudness level in stapedotomy with or without stapedial tendon preservation.Methods: A prospective observational study was conducted in the Department of Otolaryngology-Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka for 18 months in patients with otosclerosis. Total 30 subjects were selected based on the inclusion and exclusion criteria. All patients were assessed pre-operatively by clinical examination, otoscopy and microscopic examination. Hearing was assessed by pure tone audiometry. Uncomfortable level and stapedial reflex threshold were tested in all cases. The selected cases were placed into two groups. Stapedial tendon resection in Group-I and stapedial tendon preservation in Group-II. Post-operative follow up was done at 3 months and 6 months. Hearing and uncomfortable loudness level were evaluated with PTA during follow up by calculating the average of 500Hz, 1000Hz, 2000Hz and 4000HZ. The data were calculated manually. The statistical significance was set to P< 0.05. Results of the study were expressed as mean, standard deviation (± SD), frequency and percentages. Means and standard deviations were reported for continuous variables. Frequencies and percentages were reported for categorical variables. Unpaired Student’s t test was done to compare the continuous variables and Chi Square test was done to compare the categorical variables.Results: In this study preoperative average ABG for group I and group II were 35 ± 4.57 dB and 34 ± 4.17 dB respectively. In group I, post operative average ABG after 3 months and 6 months were 14 ± 3.7 dB and 13±3.3 dB respectively. Post operative average ABG after 3 months was 13 ± 5.7 dB and was 12 ± 4.4 dB for group II. But the hearing improvement between two groups was not statistically significant. In case of preoperative mean UCL was 95 ± 1.8 dB and 96 ± 2.5 dB for group I and group II respectively. Postoperative mean UCL after 3 months was 96 ± 3.57 dB and after 6 months was 99 ± 6.28 dB in group I. For group II, postoperative mean UCL after 3 months and 6 months was 107±4.2 dB and 113 ± 3.2 dB respectively. Here mean UCL was on average 11 dB higher for group II in 3 months and additional 6 dB improvement noted after 6 months, but show minimal change in group I. This finding was statistically significant.Conclusion: Preservation of the stapedial tendon is the choice in the surgical treatment of otosclerosis which helps to improve functional outcomes as well as to provide the more physiologic protection of middle ear. Postoperative discomfort threshold levels were increased in patients who had their stapedial tendon restored.Bangladesh J Otorhinolaryngol 2021; 27(2): 117-123